Pengembangan Bahan Ajar E-Book Berbasis Project Based Learning dalam Menguatkan Literasi Sains pada Siswa SD - Retno Martalia; Pinkan Amita Tri Prasasti; Naniek Kusumawati (PUSAT PENELITIAN DAN PENGABDIAN MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2022)
This study aims to develop teaching materials in the form of E-Books based on PBL (Project Based Learning) to strengthen scientific literacy in class VI SDN Pilangbango Madiun City as one of the easy-to-use learning media. This research uses R&D development research using the Borg And Gall model. Data collection techniques using observation, questionnaires, and documentation. The results showed that: (1) the development of teaching materials in the form of E-Books based on PBL (Project Based Learning), namely information gathering, planning, developing initial products, and initial field tests which were validated by 3 expert validators and teacher or student responses, product analysis and revision. stage I. (2) Testing the feasibility of the results of the validation of experts, the responses of teachers and students get the